Molecular Dynamics Simulation Estrogen Receptor Alpha againts Andrographolide as Anti Breast Cancer - Doni Dermawan; Riyadi Sumirtanurdin; Deti Dewantisari (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Breast cancer is the most common cancer suffered by women with 1.67 million new cases in the world by 2012 with a mortality rate of 12.9%. Tamoxifen is a standard therapy for breast cancer but can cause endometrial and thromboembolic cancer. Andrografolid is an active compound from  Andrographis paniculata which has antiproliferation activity of MCF-7 breast cancer cells with IC50 was 61.11 μM. The purpose of this study was to design andrographolide modification structures as human estrogen receptor alpha (hER-α) antagonists. Molecular docking simulation results showed that the andrographolide and AND5 (best andrographolide derivative) have free binding energy (ΔG) values were -9.65 kcal/mol and -12.43 kcal/mol, respectively, and hydrogen bonds were formed with Gly521, Asp351, and Met343. The ΔG value of ANDS was lower than tamoxifen (-11.40 kcal/mol). Pharmacophore modeling results showed that andrographolide and AND5 had a high pharmacophore-fit value of 46.39% and 63.47%, respectively. Molecular dynamics simulation using MM-PBSA calculation method, showed that the hERα-AND5 system has a value of ΔGTOTAL = -50.52 kcal/mol compared to the hERα-estradiol system as an agonist with a value of ∆GTOTAL = -40.86 kcal/mol . These results suggested that AND5 has better affinity for hERα compared to estradiol so that AND5 is a very promising anti breast cancer agent.Keywords: Andrographolide, molecular dynamics, breast cancer, molecular docking, estrogen receptor alpha